Preparation of anodized aluminium oxide at high temperatures using low purity aluminium (Al6082) - Kozhukhova, A.E.; du Preez, S.P.; Bessarabov, D.G. (Surface & coatings technology, 2019)
A rapid two-step anodization process was developed to prepare semi-ordered nanoporous anodized aluminium oxide (AAO) layers using an inexpensive aluminium (Al) alloy, Al6082 (97.53% Al) as the Al source material. Al anodizing was performed at various anodization voltages (30, 45, 60 V) and temperatures (20, 30, 40 °C) using 0.4 M oxalic acid as the electrolyte. The effects of temperature and voltage on the morphological characteristics of the obtained AAO formed by one- and two-step anodization were investigated. The obtained AAO surfaces were characterized by scanning electron microscopy. Morphological characteristics of importance here were the pore diameter, inter-pore distance, porosity and pore density. An AAO layer with a semi-ordered pore arrangement was prepared using a two-step anodization process, which included an AAO etching step before the second anodization. The obtained AAO had a pore diameter of 43.8 ± 6.0 nm, inter-pore distance of 82.6 ± 19 nm, 25% porosity, pore density of 169 pores/μm2 and layer thickness of 53 μm. Energy-dispersive X-ray spectroscopy results suggested that non-Al elements present in Al6082 were present on the surface of AAO. From an economic perspective, the AAO preparation process proposed in this study makes the fabrication of AAO more attractive. •AAO layers have been prepared by anodization of Al6082 at elevated temperatures.•Al6082 as the Al source material significantly decreases AAO preparation cost.•Two-step anodization process yields AAO layer with semi-ordered pore arrangement.•Etching time greatly affects AAO pore arrangement.•Non-Al elements present in Al6082 did not significantly affect the AAO layer morphology.